ZIP Kinase Triggers Apoptosis from Nuclear PML Oncogenic Domains - Kawai, Taro (American Society for Microbiology, 2003)
PML oncogenic domains (PODs), also referred to as nuclear dot 10 bodies, Kreb's bodies, or nuclear bodies, represent nuclear structures implicated in the regulation of a variety of cellular processes, including transcription, tumor suppression, and apoptosis. ZIP kinase (ZIPK) is a proapoptotic protein kinase with homology to DAP kinase, a protein kinase implicated in apoptosis. We show here that ZIPK is present in PODs, where it colocalizes with and binds to proapoptotic protein Daxx. Arsenic trioxide (As(2)O(3)) and gamma interferon (IFN-γ), which accentuate POD formation, increased the association of ZIPK with PODs. In contrast, the kinase-inactive ZIPK resides in nuclei with a diffuse pattern and significantly prevents the association of Daxx with PODs, implying that ZIPK recruits Daxx to PODs via its catalytic activity. ZIPK also binds and phosphorylates proapoptotic protein Par-4. Association of ZIPK with Daxx was enhanced by coexpression of Par-4. Activation of caspases and induction of apoptosis were also observed in cells overexpressing these proteins. Conversely, small-interfering RNA-mediated reduction of ZIPK, Daxx, or Par-4 expression decreased activation of caspase and apoptosis induced by As(2)O(3) and IFN-γ. These results suggest that ZIPK, in collaboration with Daxx and Par-4, mediates a novel nuclear pathway for apoptosis.